Effects of packaging materials and storage conditions on storability of pepper (Capsicum frutescens L.) fruits - Adewoyin , O B (Journal of Postharvest Technology, 2017)
Pepper is a perishable seasonal vegetable fruit that requires appropriate postharvest handling and storage to extend its shelf-life and preserve quality of the Pepper Fruit (PF). However, there is dearth of information on its handling and storage in Southwest Nigeria. Pepper grown in the organic field, Teaching and Research Farm, Federal University University, OyeEkiti were harvested with and without pedicels at 10 and 100% ripeness. Postharvest handling was evaluated by comparing packaging in perforated polyethylene, non-perforated polyethylene and aluminium-foil before storing in either Ambient Conditions (AC) of 21.9-33.5°C and 58-62% Relative Humidity (RH); Refrigerator (4.0°C and 40-45% RH) or Evaporative Coolant Structure (ECS) (10.0-15.8°C and 70-75% RH). Percentage Weight Loss (WL) was calculated. Firmness (FM) and Decay Level (DL) were evaluated on a scale of 1 to 4 and General Appearance (GA) on scale of 1 to 5. Data were analysed using correlation coefficient and ANOVA at p <0.05. The shelf-life of PF harvested with pedicels at 10% ripeness and stored in refrigerator, ECS and AC was 27, 20 and 6 days respectively while shelf life of PF harvested at 100% ripeness was 21, 14, and 3 days, respectively. In contrast, the shelf life of PF harvested without pedicel at 10% ripeness was 21, 18 and 5 days while for 100% ripeness, it was 18, 15 and 2 respectively. The WL, DL, GA and firmness of fruits harvested at 10% with pedicels and stored in refrigerator was 14.0%, 3.0, 4.0 and 3.5. The PF packaged in the aluminium-foil had significantly longer (30 days) shelf life than those packaged in perforated polyethylene (21 days) and non perforated polyethylene (15 days). Storability of PF was best at 10% ripeness with pedicel.